Method for preparing copper-nickel alloy for solid-state battery through acidic system

The preparation of copper-nickel alloys by acidic system electrodeposition method solves the corrosion problem of copper foil in solid-state lithium batteries, and realizes high-strength and high-elongation copper-nickel alloys suitable for sulfide solid-state batteries, thus improving battery life and performance.

CN120866896APending Publication Date: 2025-10-31MEIZHOU JIATAI TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510984835.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-17
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

In existing solid-state lithium batteries, copper foil is easily corroded by electrolytes, resulting in a short service life and low tensile strength, making it difficult to meet the requirements of negative electrode current collectors. Furthermore, copper-nickel alloys in sulfide solid-state batteries are prone to side reactions with metallic lithium negative electrodes, leading to a thickening of the interface passivation layer and affecting battery performance.

Method used

A copper-nickel alloy with a tensile strength greater than 1000 MPa was prepared by an acidic electrodeposition method using copper sulfate pentahydrate and nickel sulfate hexahydrate as raw materials, sodium citrate or sodium citrate and sodium tartrate as complexing agents, combined with buffers and conductive salts, and by controlling electrolyte parameters such as temperature, current density and pH value.

Benefits of technology

The prepared copper-nickel alloy has high tensile strength and elongation, suppresses side reactions, is suitable for sulfide solid-state batteries, has a simple process, low cost, is suitable for large-scale production, has uniform coating thickness, and excellent corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120866896A_ABST
    Figure CN120866896A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a copper-nickel alloy for a solid-state battery through an acidic system, and belongs to the technical field of solid-state batteries. Preparing a copper-nickel alloy by adopting an electro-deposition method; the electrolyte comprises the following components: copper sulfate pentahydrate and nickel sulfate hexahydrate as raw materials, sodium citrate as a single complexing agent or a mixed complexing agent consisting of sodium citrate and sodium tartrate, a buffering agent, conducting salt and a brightener. According to the method, the components and the thickness of the alloy are adjusted by adjusting the type and the input amount of the complexing agent and changing technological parameters (the electrolyte temperature, the current density and the like), and the copper-nickel alloy with the tensile strength higher than 1000 MPa, the ductility higher than 3.97% and the high nickel content can be prepared. The electrochemical electrolysis preparation technology is simple, high temperature is not needed, the production cost is low, the product impurity content is low, the obtained copper-nickel alloy is excellent in corrosion resistance, the coating thickness is uniform, electro-deposition can be conducted at the normal temperature, energy is saved, and the method is suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid-state battery technology, specifically relating to a method for preparing copper-nickel alloys for solid-state batteries using an acidic system. Background Technology

[0002] Solid-state batteries are considered a key direction for next-generation battery technology due to their advantages such as high safety, high energy density, and long lifespan. Current solid-state lithium batteries generally use copper foil as the negative electrode current collector. However, copper foil is easily corroded by the electrolyte in solid-state lithium batteries, resulting in a short lifespan and thus reducing the overall lifespan of the solid-state lithium battery. Furthermore, the tensile strength of current copper foil is below 1000 MPa, which is insufficient to meet the requirements for negative electrode current collectors in solid-state lithium batteries.

[0003] The application of copper-nickel alloys in sulfide solid-state batteries has significant potential implications: Firstly, it can improve interfacial stability. While sulfide solid-state electrolytes possess high ionic conductivity, they are prone to side reactions with the lithium metal anode, leading to thickening of the interfacial passivation layer and capacity decay. Copper-nickel alloys, due to their chemical inertness, can suppress these side reactions; specifically, the lower oxidation tendency of Ni in copper-nickel alloys and the easy formation of a dense oxide layer on the surface inhibit direct reactions with sulfide electrolytes. Secondly, copper-nickel alloys possess high conductivity and high mechanical properties. Sulfide solid-state batteries require highly conductive current collectors to support rapid charge and discharge while withstanding mechanical stresses caused by electrode volume changes. Furthermore, under the same high tensile strength conditions, copper-nickel alloys exhibit better ductility than pure copper, which can suppress current collector breakage caused by the volume expansion of electrode active materials (such as sulfur or silicon) during cycling.

[0004] The standard electrode potential of copper is 0.337V, while that of nickel is -0.25V, with copper having a potential approximately 0.6V higher than nickel. The deposition potentials of the two co-deposited metals must be very close. If the difference is too large, the metal with the more positive potential will be preferentially deposited, and may even completely repel the deposition of the metal with the more negative potential, thus preventing the formation of an alloy coating. Therefore, it is essential to research a process to achieve the co-deposition of copper and nickel metal ions and develop a copper-nickel alloy with a tensile strength greater than 1000 MPa and an elongation greater than 3% suitable for sulfide solid-state batteries. Summary of the Invention

[0005] To address the aforementioned problems in the prior art, this invention provides a method for preparing copper-nickel alloys for solid-state batteries using an acidic system.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] This invention provides a method for preparing copper-nickel alloys for solid-state batteries using an acidic system. The copper-nickel alloy is prepared by electrodeposition. The electrolyte includes the following components: copper sulfate pentahydrate and nickel sulfate hexahydrate as raw materials, sodium citrate as a single complexing agent or a mixed complexing agent composed of sodium citrate and sodium tartrate, and also includes a buffer, a conductive salt, and a brightener.

[0008] As a preferred embodiment of the present invention, the buffer includes boric acid, the conductive salt includes sodium chloride, and the brightener includes sodium saccharin.

[0009] As a preferred embodiment of the present invention, the concentrations of each component in the electrolyte are as follows: copper sulfate pentahydrate: 20-28 g / L, nickel sulfate hexahydrate: 85-95 g / L; when sodium citrate is used as a single complexing agent, the concentration of sodium citrate is 170-190 g / L; when a mixed complexing agent composed of sodium citrate and sodium tartrate is used, the concentration of sodium citrate is 170-190 g / L, the concentration of sodium tartrate is 55-65 g / L, boric acid is 10-20 g / L, sodium chloride is 7-12 g / L, and sodium saccharin is 4-7 g / L.

[0010] As a preferred embodiment of the present invention, the electrolyte has a circulation rate of 500-800 mL / min and a pH value of 3-5.

[0011] As a preferred embodiment of the present invention, when preparing copper-nickel alloys by electrodeposition, the current density is 8.0–12.0 A / dm³. 2 The electrolyte temperature is 50–55℃, the electrodeposition time is 300–1500 s, and the rotation speed is 600–800 r / min.

[0012] As a preferred embodiment of the present invention, the copper-nickel alloy for solid-state batteries has a thickness of 4.5 to 18 μm, a nickel content of 10 to 20 wt%, and a tensile strength > 1000 MPa.

[0013] The present invention also provides a copper-nickel alloy prepared by a method for preparing a solid-state battery copper-nickel alloy according to the above-described acidic system.

[0014] This invention also provides an application of the copper-nickel alloy described above in the preparation of solid-state batteries, particularly in the preparation of sulfide solid-state batteries.

[0015] The present invention also provides a solid-state battery, which uses the copper-nickel alloy described above as the negative electrode current collector.

[0016] As a preferred embodiment of the present invention, the solid-state battery is a sulfide solid-state battery.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) This invention adjusts the composition and thickness of the alloy by adjusting the type and amount of complexing agent and changing the process parameters (electrolyte temperature, current density, etc.), and can prepare copper-nickel alloys with tensile strength higher than 1000MPa, high elongation and high nickel content.

[0019] (2) The electrochemical electrolysis preparation process of the present invention is simple, does not require high temperature, has low production cost, and the product has low impurity content. The obtained copper-nickel alloy has excellent corrosion resistance and uniform coating thickness. Electrodeposition can be carried out at room temperature, saving energy and suitable for large-scale industrial production. It is an alloy preparation technology with broad application prospects. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 This is a process flow diagram of Example 1;

[0022] Figure 2 The tensile strength diagrams for the copper-nickel alloys obtained at different electrolyte temperatures in Example 1 are shown.

[0023] Figure 3 The tensile strength diagrams of the copper-nickel alloy foils obtained under different current densities in Example 2 are shown.

[0024] Figure 4 In Example 2, when sodium citrate was used as the single complexing agent, the temperature was 50–55°C and the current was 10 A / dm. 2 SEM images of copper-nickel alloys prepared under conditions of pH = 3.6–3.7;

[0025] Figure 5 In Example 2, when sodium citrate was used as the single complexing agent, the temperature was 50–55°C and the current was 10 A / dm. 2 XRD patterns of copper-nickel alloys prepared under conditions of pH = 3.6–3.7;

[0026] Figure 6 The tensile strength diagrams are shown for the copper-nickel alloys obtained at different electrolyte temperatures in Example 3.

[0027] Figure 7 The tensile strength diagrams of the copper-nickel alloy foils obtained under different current densities in Example 4 are shown.

[0028] Figure 8In Example 4, when sodium citrate and sodium tartrate were used as a mixed complexing agent, the temperature was 50–55°C and the current was 10 A / dm. 2 SEM images of copper-nickel alloys prepared under conditions of pH = 4.50–4.60;

[0029] Figure 9 In Example 4, when sodium citrate and sodium tartrate were used as a mixed complexing agent, the temperature was 50–55°C and the current was 10 A / dm. 2 XRD patterns of copper-nickel alloys prepared under conditions of pH = 4.50–4.60. Detailed Implementation

[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.

[0031] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included within this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0032] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0033] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0034] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0035] The raw materials used in the following embodiments are all commercially available and conventional, and are not particularly limited. In the following embodiments, electrodeposition is performed with a rotating cathode. Anodes, consisting of five copper plates and one nickel plate, are hung on a beaker containing electrolyte. The beaker is then heated to a specified temperature using a water bath. The cathode is placed in the middle of the heated electrolyte, so that it is just submerged in the electrolyte. The six anodes are connected by wires, and a copper-nickel alloy is obtained by rotating the cathode using a DC regulated power supply in constant current mode. This will not be described again below.

[0036] Example 1

[0037] The preparation method of copper-nickel alloy foil for solid-state batteries includes the following steps.

[0038] The experiments were conducted at temperatures of 40–45°C, 50–55°C, and 60–65°C (temperature fluctuations occurred during the experiment, and three parallel experiments were performed for each temperature range), with a current density of 10 A / dm². 2 Copper-nickel alloy foil was prepared under the following conditions: the electrolyte composition and concentration were as follows: 24 g / L copper sulfate pentahydrate (CuSO4·5H2O) and 90 g / L nickel sulfate hexahydrate (NiSO4·6H2O) as raw materials, 180 g / L anhydrous sodium citrate (C6H5Na3O7) as complexing agent, 15 g / L boric acid (H3BO3) as buffer, 9 g / L sodium chloride (NaCl) as conductive salt, and 6 g sodium saccharin (C7H4NO3SNa). The pH of the electrolyte was 3.6–3.7 (the normal fluctuation range of pH during the experiment). The Cu-Ni alloy coating was prepared by electrodeposition, and the electrodeposition time was 15 min.

[0039] The process flow diagram of this embodiment is as follows: Figure 1 As shown, the tensile strength of the obtained copper-nickel alloy is as follows: Figure 2 As shown in Table 1, the nickel content measured by atomic absorption spectrometry is as follows. It can be seen that the nickel content is highest at temperatures of 50–55℃, therefore, the copper-nickel alloy prepared at this temperature has the best tensile strength.

[0040] When the electroplating current is 10A / dm 2When the pH is 3.6–3.7 and the electrolysis temperature is 40–45℃, the resulting copper-nickel alloy foil has obvious copper powder on its surface and a dull color. When the electrolysis temperature is 50–55℃, the resulting copper-nickel alloy has a smooth, flat, and bright surface. When the electrolysis temperature is 60–65℃, the resulting copper-nickel alloy foil has sparse pitting on its surface and more charred areas at the edges. This is because the reduction activation energy of copper is lower than that of nickel. When the temperature is too low, the temperature has little effect on the reduction of copper. At the same time, nickel ions near the cathode cannot be replenished in time due to the slow reduction rate, further inhibiting nickel deposition, thus causing the alloy surface to become rough and copper powder to appear. When the temperature is too high, it may be because the deposition rate is too fast, causing dendrite growth, resulting in small spots on the foil surface.

[0041] Table 1. Nickel content of copper-nickel alloy foil at different temperatures.

[0042]

[0043] In this embodiment, when the temperature is 40-45℃, the thickness of the obtained copper-nickel alloy foil is 4.5-18 μm, with the best performance being a tensile strength of 996.6 MPa, an elongation of 3.97%, and a nickel mass fraction of 9.82%. When the temperature is 50-55℃, the thickness of the prepared copper-nickel alloy foil is 4.5-18 μm, with a nickel mass fraction of 13.17%. Testing shows that the nickel grains are uniformly doped into the copper grains, the surface roughness Rz is 1.43 μm, and the best performance is a tensile strength of 1457.07 MPa, an elongation of 3.97%, uniform thickness, and no tearing bands. When the temperature is 60-65℃, the prepared copper-nickel alloy foil has a dull surface color, a thickness of 4.5-18 μm, and the best performance is a tensile strength of 1146.3 MPa, an elongation of 3.97%, and a nickel mass fraction of 9.60%.

[0044] Example 2

[0045] Compared with Example 1, the difference lies in setting the electrolyte temperature to 50-55°C and changing the electroplating current density to 5, 10, and 15 A / dm³, respectively. 2 Three parallel experiments were set up for each current density.

[0046] In this embodiment, the current was found to be 5A / dm. 2 The alloy foil has a reddish surface with small areas of silvery-white at the edges, and the entire sheet is relatively thin; the current is 10A / dm². 2 The alloy foil has a smooth, flat, and bright surface; the current is 15A / dm. 2The alloy foil surface showed a significant amount of copper powder and pitting, and the entire sheet was brittle, with small areas of charring at the edges. This was because when the current was too low, the cathode potential was insufficient to fully reduce nickel ions, causing copper ions to be preferentially deposited, preventing the co-deposition of copper and nickel ions and resulting in the metal foil appearing red. When the current was 15 A / dm³... 2 At this time, the current density is too high, exceeding the limiting diffusion current density of copper, resulting in copper oxide inclusions on the coating surface and failure to achieve copper-nickel co-deposition.

[0047] The tensile strength of copper-nickel alloy foils obtained at different current densities is as follows: Figure 3 As shown.

[0048] In summary, when sodium citrate is used as the single complexing agent, the optimal temperature is 50–55°C and the current is 10 A / dm. 2 A copper-nickel alloy with a smooth, flat, and bright surface and optimal performance was prepared under pH conditions of 3.6–3.7. Its tensile strength reached 1500 MPa, elongation was 3.97%, and the nickel content was determined to be 13.17% by atomic absorption spectrometry. The SEM image of the copper-nickel alloy prepared under these conditions is shown below. Figure 4 As shown, the XRD pattern is as follows Figure 5 As shown. By Figure 5 It can be seen that the peaks of the copper-nickel alloy sample obtained under optimal conditions are all between the peaks of copper and nickel in the standard chart, indicating that the synthesized sample is an alloy.

[0049] Example 3

[0050] Compared with Example 1, the difference is that sodium citrate and sodium tartrate were used as mixed complexing agents, the concentration of sodium citrate in the electrolyte was 180 g / L and the concentration of sodium tartrate was 60 g / L, and the pH of the electrolyte was 4.50 to 4.60 (the normal fluctuation range of pH during the experiment).

[0051] The results showed that when the fixed current density was 10 A / dm 2 At pH values ​​of 4.50–4.60, copper-nickel alloys prepared at different temperatures all exhibited pitting on their surfaces. However, the alloy obtained at 50–55°C showed the best appearance, with fewer and smaller pits. Coatings obtained at temperatures above 60°C showed a greater amount of copper powder on their surfaces, and the entire foil was relatively brittle. This may be because the excessively high current density caused a hydrogen evolution reaction at the cathode, leading to a localized increase in pH and the formation of CuO that adhered to the foil surface.

[0052] The effect of different temperatures on the tensile strength of copper-nickel alloy foil, as follows: Figure 6 As shown in Table 2, the nickel content of copper-nickel alloy foils obtained at different temperatures is shown in Table 2.

[0053] Table 2 Effect of different temperatures on the nickel content of copper-nickel alloy foil

[0054]

[0055] In this embodiment, when the temperature is 40–45°C, the prepared copper-nickel alloy foil has a thickness of 4.5–18 μm, with optimal properties of a tensile strength of 639.35 MPa, an elongation of 4.6%, and a nickel mass fraction of 14.39%. When the temperature is 50–55°C, the prepared copper-nickel alloy foil has a smooth and bright surface, a thickness of 4.5–18 μm, and a nickel mass fraction of 28.48%. Testing showed that nickel grains were uniformly doped into copper grains, with a surface roughness Rz of 1.51 μm, a tensile strength of 1300 MPa, an elongation of 3.97%, uniform thickness, and no tearing bands. When the temperature exceeds 60°C, a significant amount of copper powder appears on the surface of the resulting coating, with optimal properties of a tensile strength of 706.43 MPa, an elongation of 4.1%, and a nickel mass fraction of 18.73%.

[0056] Example 4

[0057] Compared with Example 3, the difference lies in setting the electrolyte temperature to 50-55°C and changing the electroplating current density to 5, 10, and 15 A / dm³ respectively. 2 This embodiment found that when the temperature is fixed at 50–55°C and the pH is 4.50–4.60, the current has a significant impact on the copper-nickel alloy. The current is 5 A / dm. 2 and 15A / dm 2 The alloy surface at that time had a lot of red or black copper powder, especially from 5A / dm 2 The prepared alloy foil is more brittle, possibly due to the uneven distribution of cathode current density, caused by Cu + A higher potential preferentially leads to deposition at higher current densities, forming localized copper-rich regions. (15 A / dm²) 2 The alloy was likely produced because the current density was too high, causing CuO to form on the cathode and adhere to the foil surface. (10 A / dm) 2 The prepared alloy coating has a smooth and bright surface with few pits.

[0058] Figure 7 The tensile strength of copper-nickel alloy foils obtained with different currents.

[0059] In summary, when sodium citrate and sodium tartrate are used as a mixed complexing agent, a temperature of 50–55℃ and a current of 10 A / dm are suitable. 2A copper-nickel alloy with a smooth, flat, and bright surface and optimal performance was prepared under pH conditions of 4.50–4.60. Its tensile strength reached 1300 MPa, its elongation was 3.97%, and its nickel content was 28.48% as determined by atomic absorption spectrometry. Figure 8 Here is a SEM image of the copper-nickel alloy obtained under these conditions. Figure 9 The image shows the XRD pattern of the copper-nickel alloy obtained under these conditions.

[0060] Depend on Figure 4 and Figure 8 It can be seen that, under different complexing agents, the copper-nickel alloy sample obtained under the optimal conditions has coarser grains, more uniform grain distribution, smooth surface, and good density.

[0061] Depend on Figure 5 and Figure 9 It can be seen that, under different complexing agents, the peaks of the copper-nickel alloy samples obtained under the optimal conditions are all between the peaks of copper and nickel in the standard chart, indicating that the synthesized samples are alloys.

[0062] The above description is merely a preferred embodiment of the present invention, and the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing a copper-nickel alloy for solid-state batteries using an acidic system, characterized in that, Copper-nickel alloys are prepared by electrodeposition. The electrolyte includes the following components: copper sulfate pentahydrate and nickel sulfate hexahydrate as raw materials, sodium citrate as a single complexing agent or a mixed complexing agent composed of sodium citrate and sodium tartrate, and also includes a buffer, a conductive salt and a brightener.

2. The method for preparing copper-nickel alloy for solid-state batteries using an acidic system according to claim 1, characterized in that, The buffer includes boric acid, the conductive salt includes sodium chloride, and the brightener includes sodium saccharin.

3. The method for preparing copper-nickel alloy for solid-state batteries using an acidic system according to claim 2, characterized in that, The concentrations of each component in the electrolyte are as follows: copper sulfate pentahydrate: 20–28 g / L, nickel sulfate hexahydrate: 85–95 g / L; when sodium citrate is used as a single complexing agent, the concentration of sodium citrate is 170–190 g / L; when a mixed complexing agent composed of sodium citrate and sodium tartrate is used, the concentration of sodium citrate is 170–190 g / L and the concentration of sodium tartrate is 55–65 g / L; boric acid 10–20 g / L, sodium chloride 7–12 g / L, and sodium saccharin 4–7 g / L.

4. The method for preparing copper-nickel alloy for solid-state batteries using an acidic system according to claim 1, characterized in that, The electrolyte has a circulation rate of 500–800 mL / min and a pH value of 3–5.

5. The method for preparing copper-nickel alloy for solid-state batteries using an acidic system according to claim 1, characterized in that, When preparing copper-nickel alloys using electrodeposition, the current density is 8.0–12.0 A / dm³. 2 The electrolyte temperature is 50–55℃, the electrodeposition time is 300–1500 s, and the rotation speed is 600–800 r / min.

6. The method for preparing copper-nickel alloy for solid-state batteries using an acidic system according to claim 5, characterized in that, The copper-nickel alloy used in solid-state batteries has a thickness of 4.5–18 μm, a nickel content of 10–20 wt%, and a tensile strength >1000 MPa.

7. A copper-nickel alloy prepared by a method for preparing a solid-state battery using an acidic system according to any one of claims 1 to 6.

8. The application of the copper-nickel alloy according to claim 7 in the preparation of solid-state batteries.

9. A solid-state battery, characterized in that, The copper-nickel alloy described in claim 7 is used as the negative electrode current collector.